2008
DOI: 10.1016/s0210-4806(08)73980-9
|View full text |Cite
|
Sign up to set email alerts
|

Nuestra experiencia con minicintas (TVT Secur y MiniArc) en la cirugía de la incontinencia urinaria de esfuerzo

Abstract: These new tapes show fewer complications that the TVT-O and TOT tapes and allow the possibility of placement with local anesthesia but further studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…In association with this, Fischer et al reported that patient satisfaction with TOT was 90% after 1 year of follow-up [12]. Other authors reported that patient satisfaction with TVT-S was 76.4% to 80% after 1 year of follow-up [13,16], which agrees with this study of the TVT-S procedure.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In association with this, Fischer et al reported that patient satisfaction with TOT was 90% after 1 year of follow-up [12]. Other authors reported that patient satisfaction with TVT-S was 76.4% to 80% after 1 year of follow-up [13,16], which agrees with this study of the TVT-S procedure.…”
Section: Discussionsupporting
confidence: 82%
“…However, according to previous studies, complications such as urethral or bladder perforation, vascular damage, and vaginal erosion are still reported [21,22]. According to another study, following the TVT-S procedure, complications such as vaginal wall perforation and urinary tract infection occurred [13,15,16]. In our study, however, no significant complications occurred after TVT-S or MONARC.…”
Section: Discussionmentioning
confidence: 38%
“…Synthetic slings have increasingly been used for treating female SUI [1–8,11–14] , and although these commercially available kits are highly effective their cost-effectiveness has been questioned [15–17] . To reduce this cost many surgeons have used ‘off-the-shelf’ polypropylene mesh and tailored it as a mid-urethral tape [15–19] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are potential vascular and neurological complications related to the passage of needles through the obturator foramen [6] . Thus mini-slings (i.e., the TVT-Secur or MiniArc) were introduced to further reduce these potential complications [7] . A more recent technique in the use of mid-urethral tapes was the Contasure needle-less technique (Neomedic International, Inc., Spain).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 83.1% and 77.6% of 97 patients who received MiniArc-Sling procedures showed no urine leakage in a cough provocative test at 6 weeks and 12 months after surgery, respectively, with significant improvements in 69.1% of the patients' quality of life [24]. According to a comparative study of the TVT SECUR and MiniArc-Sling procedures, the objective cure rate was 80.4% and 90.2%, respectively, but the average follow-up period differed at 11 months and 3.5 months for each group, respectively [25]. In our study, the cure rates for the TVT SECUR group and the CureMesh group were 68.4% and 77.3%, respectively, and improvements in symptoms were 18.4% and 13.6%, respectively, showing similar results to previous studies and no significant differences between the two groups.…”
Section: Discussionmentioning
confidence: 99%